Polish and Finnish nursing students’ attitudes, knowledge and skills related to research utilisation - Asta Heikkilä; Katarzyna Kwiecień-Jaguś; Maija Hupli; Johanna Kero; Jouko Katajisto; Leena Salminen; Helena Leino-Kilpi (Instytut Medycyny Wsi im. Witolda Chodzki, 2025)
Introduction:
Evidence-based practice and research utilisation at its core are essential for high quality patient care. In this study, research utilization is defined as a process involving acquisition, critical reading (including evaluation) and application of research knowledge. The translation of research knowledge into clinical nursing practice, however, is often hampered, primarily due to nurses’ lacking competence for research utilization.
Objective:
The aim of this study is to assess and compare graduating nursing students’ attitudes, knowledge and skills related to research utilisation in two European countries.
Material and methods:
Data was collected in Poland (n=168) and Finland (n=260) using the Competence in Research Utilisation instrument, and analysed statistically.
Results:
Students in both countries had positive attitudes to research utilisation. Polish students’ attitudes were more positive. A knowledge test revealed poor knowledge of research utilisation in both countries. Students assessed their research utilisation skills as above moderate, but Polish students rated their skills higher.